Model Pembelajaran High Scope Pendidikan Anak Usia Dini - Nanik Rahayu; Saniyya Putri H; Masitha Nunlehu; Mia Sumiani Madi; Nita Priyanti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
In High (Scope) learning, children get direct playing experience because they are actively involved in learning through the use of various existing game tools, the learning environment is divided into several corners or areas both indoors and outdoors, the people involved in learning and the ideas that arise are expected that the child will gain a number of useful knowledge to develop all aspects of his development optimally. Preschoolers learn to make their own plans and practice implementing them so that children can acquire the knowledge and skills needed to build a solid foundation for their later development and learning. This article aims to describe the High Scope learning model. The method used for data collection is in the form of a literature study, namely a method that can study various reference books and similar previous research results.